If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
2-(4*(1/9)*x) = -6 // + 6
2-(4*(1/9)*x)+6 = 0
(-4/9)*x+2+6 = 0
8-4/9*x = 0 // - 8
-4/9*x = -8 // : -4/9
x = -8/(-4/9)
x = 18
x = 18
| 8x+6y=46 | | 4*[4+(5-1)*2]-20*2= | | 5x+6y=38 | | 21-20y=21 | | d=50t | | 23/4=-63/5y | | x^2/2 | | 20=8-x | | 2x^2/4 | | 100x-20x=30 | | 1/3h=-1/2h-5 | | -2x-y=1 | | -65=5+8x | | 2/(x-3)^2 | | 6+(-4)(3)= | | 5/2s-2 | | 3x/5x | | 60+9x= | | y=(4x)/(1+x) | | 2(7x-1)=-114 | | y+3/4x-1 | | 8=5-12 | | -2x-6+6x=10 | | 7x+1=-7x-167 | | -8x-15=-151 | | 7r^3+28r^2=84r | | -8+2x-x=-6 | | 5e^2-5e-30= | | 5x-9=-49 | | 3b^2-24b-144=0 | | 6c^2+7c-5= | | 4x+9=-55 |